Assessing Religious Character Among Muslim University Students in Yogyakarta Indonesia - Rukiyati, Rukiyati; Mami Hajaroh; Siti Irene Astuti Dwiningrum; Betania Kartika (Jurnal Pendidikan Agama Islam, 2025)
Purpose - In an age where technical competence often eclipses moral depth, religious character education in higher education emerges as a vital response to the erosion of empathy, integrity, and social responsibility.  This research aimed to assess the level and dimensions of religious character among moslem students at a state university in Yogyakarta, Indonesia. Design/methods/approach - The ex-post facto study involved 468 Muslim students, sampled from a population of 16,802 at a Yogyakarta state university using faculty based cluster sampling. Data were gathered via Likert-scale based questionnaires specifically developed to asses six core dimensions of religious character. Its validity and reliability were rigorously tested using Confirmatory Factor Analysis (CFA) and Structural Equation Modeling (SEM) yielding a high reliability coefficient (α = 0.95). Finding - This research emphasizes that the religious character of students cannot be reduced to a single aspect, but consists of six interrelated dimensions: cognitive/intellectuality, belief, commitment, ritual,  religious experiences, consequences. Research implications/limitations - This study offers a novel multidimensional framework for character education that can be operasionalized for assesment, curriculum design, and pedagogical intervention across diverse educational context. Originality/value - This research can help in the development of a religious education curriculum in university that is more effective and relevant to the needs of students